Stock Market Liberalizations : Financial and Macroeconomic Implications - Funke, Norbert (IMF Working Papers; Working Paper, 2001)
Using a panel of 27 countries, we analyze the effects of stock market liberalization on financial and macroeconomic development. We find that liberalization is associated with a short-term increase in real private investment growth of about 14 percentage points cumulatively in the four years following liberalization and a cumulative 4 percentage point increase in real GDP per capita growth. Growth tends to be higher if institutional reforms precede liberalization. In contrast to other studies, we also find evidence for a permanent growth effect of about 0.4 percent a year in an extended sample of 72 countries.